Alzheimer's disease: early alterations in brain DNA methylation at ANK1, BIN1, RHBDF2 and other loci - De Jager, Philip L; Srivastava, Gyan; Lunnon, Katie; Burgess, Jeremy; Schalkwyk, Leonard C; Yu, Lei; Eaton, Matthew L; Keenan, Brendan T; Ernst, Jason; McCabe, Cristin; Tang, Anna; Raj, Towfique; et al. (Nature neuroscience, 2014)
Aging can lead to cognitive decline associated with neural pathology and Alzheimer's disease (AD). Here the authors scan the methylation status of CpGs across the entire genome of brain samples from aged subjects in an epigenome-wide association study (EWAS). Several loci, including ANK1, were associated with AD pathology, gene expression and AD genetic risk networks. We used a collection of 708 prospectively collected autopsied brains to assess the methylation state of the brain's DNA in relation to Alzheimer's disease (AD). We found that the level of methylation at 71 of the 415,848 interrogated CpGs was significantly associated with the burden of AD pathology, including CpGs in the ABCA7 and BIN1 regions, which harbor known AD susceptibility variants. We validated 11 of the differentially methylated regions in an independent set of 117 subjects. Furthermore, we functionally validated these CpG associations and identified the nearby genes whose RNA expression was altered in AD: ANK1 , CDH23 , DIP2A , RHBDF2 , RPL13 , SERPINF1 and SERPINF2 . Our analyses suggest that these DNA methylation changes may have a role in the onset of AD given that we observed them in presymptomatic subjects and that six of the validated genes connect to a known AD susceptibility gene network.